Antibiotic resistance markers are a necessary tool in many clinical areas - T. M. Tutchenko; O. A. Burka; Y. A. Marfina; T. Y. Tarasiuk; T. A. Illiashenko (Publishing House TRILIST, 2020)
Antibiotic resistance (AR) is one of the leading and still far from solving the problems of mankind. Implementation of strategies for controling AR at different levels is a priority task, since crisis of the possibilities of creating new antibiotics is obvious. Implementation of this strategy in the medical field consists in the rational use of antibacterial agents and hygienic control of the spread of multiresistant strains. One of the ways to rationalize the use of antimicrobial agents was WHO AWaRe classification, the purpose of which is to expand the use of narrow-spectrum antibiotics and limit the misuse of reserve groups and drugs with growing resistance levels. Implementation of these tasks is impossible without microbiological studies. Laboratory diagnostics of the infectious causes has undergone significant improvement - automation, availability of routine determination of resistance markers. The review presents the main mechanisms of AR development by common pathogens and possibility of their reflection in resistance markers. An important milestone in 2020 was the Infectious Diseases Society of America (IDSA) clinical guideline for treatment of infectious caused by common multi-resistant gram-negative bacteria. In contrast to previous clinical guidelines, this makes the prescription of antibacterial drugs primarily on information about resistance markers, antibiotic susceptibility, and also on the location of infection. The purpose of the IDSA-2020 clinical guidelines is to assist clinicians in making decisions in treatment of infections caused by extended-spectrum β-lactamase or carbapenemase-producing Enterobacteriaceae bacteria and Pseudomonas feruginosa multi-drug resistant. The review presents the main points of this clinical guideline. Thus, effective treatment of infections caused by antibiotic-resistant microorganisms is possible due to contemporary microbiological methods according to evidence-based clinical guidelines. Automated microbiological research systems significantly expand the clinical possibilities of effective treatment of infections and epidemiological control of resistant strains.